Sensitivity and specificity of DPP® Fever Panel II Asia in the diagnosis of malaria, dengue and melioidosis. Issue 8 (22nd August 2022) - Amornchai, Premjit; Hantrakun, Viriya; Wongsuvan, Gumphol; Boonsri, Chaiyaporn; Yoosuk, Sasinaphon; Nilsakul, Jiraporn; Blacksell, Stuart D.; West, T. Eoin; Lubell, Yoel; Limmathurotsakul, Direk
Abstract : Introduction. Rapid diagnostic tests (RDTs) that can facilitate the diagnosis of a panel of tropical infectious diseases are critically needed. DPP® Fever Panel II Asia is a multiplex lateral flow immunoassay comprising antigen and IgM panels for the diagnosis of pathogens that commonly cause febrile illness in Southeast Asia. Hypothesis/Gap Statement. Accuracy of DPP® Fever Panel II Asia has not been evaluated in clinical studies. Aim. To evaluate the sensitivity and specificity of DPP® Fever Panel II Asia for malaria, dengue and melioidosis. Methodology. We conducted a cohort-based case–control study. Both cases and controls were derived from a prospective observational study of patients presenting with community-acquired infections and sepsis in northeast Thailand (Ubon sepsis). We included 143 and 98 patients diagnosed with malaria or dengue based on a positive PCR assay and 177 patients with melioidosis based on a culture positive for Burkholderia pseudomallei . Controls included 200 patients who were blood culture-positive for Staphylococcus aureus, Escherichia coli or Klebsiella pneumoniae, and cases of the other diseases. Serum samples collected from all patients within 24 h of admission were stored and tested using the DPP® Fever Panel II Asia antigen and IgM multiplex assays. We selected cutoff values for each individual assay corresponding to a specificity of ≥95 %. When assessing diagnostic tests in combination, results were considered positive if either individual test was positive. Results. Within the DPP® Fever Panel II Asia antigen assay, a combination of pLDH and HRPII for malaria had a sensitivity of 91 % and a specificity of 97 %. The combination of dengue NS1 antigen and dengue antibody tests had a sensitivity of 61 % and a specificity of 91 %. The B. pseudomallei CPS antigen test had a sensitivity of 27 % and a specificity of 97 %. An odds ratio of 2.34 (95 % CI 1.16–4.72, P =0.02) was observed for the association between CPS positivity and mortality among melioidosis patients. Conclusion. The performance of the DPP® Fever Panel II Asia for diagnosis of malaria was high and that for dengue and melioidosis was relatively limited. For all three diseases, performance was comparable to that of other established RDTs. The potential operational advantages of a multiplex and quantitative point-of-care assay are substantial and warrant further investigation.